Construction of nominal ionospheric gradient using satellite pair based on GNSS CORS observation in Indonesia - Supriadi, Slamet; Abidin, Hasanuddin Zainal; Wijaya, Dudy Darmawan; Abadi, Prayitno; Saito, Susumu; Prabowo, Dwiko Unggul (Earth, planets, and space, 2022)
Ground-Based Augmentation System (GBAS) is a GNSS augmentation system that meets International Civil Aviation Organization (ICAO) requirements to support precision approach and landing. GBAS is based on local differential GNSS technique with reference stations located around an airport to provide necessary integrity and accuracy. The performance of the GBAS system can be affected by gradient in the ionospheric delay between aircraft and reference stations. A nominal ionospheric gradient, which is bounded by a conservative error bound, is represented by a parameter σ vig . The parameter σ vig is commonly determined using station pair to GNSS Continuous Operating Reference Station (CORS) data. The station-pair method is susceptible to doubling of the estimation error of receiver inter-frequency bias (IFB) and is not suitable with the CORS conditions in Indonesia. We propose a satellite-pair method that is found to be more suitable for the CORS network over Indonesia which is centered in Java and Sumatra islands. An overall value of σ vig (5.21 mm/km) was obtained using this method along with preliminary results of a comparison of σ vig from Java and Sumatra islands. Graphical Abstract